1983
DOI: 10.2527/jas1983.573553x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin E and Selenium Injections on Reproduction and Preweaning Lamb Survival in Ewes Consuming Diets Marginally Deficient in Selenium

Abstract: Medium wool ewes were injected with vitamin E and(or) Se over a 2-yr period to evaluate the influence of these treatments on reproduction. Ewes were divided randomly into four groups, consisting of a control, plus groups receiving monthly sc injections of either 272 iu vitamin E, 4 mg Se or 272 IU vitamin E plus 4 mg Se during pregnancy. Selenium administration increased (P less than .05) ewe blood Se concentrations, but had no effect (P greater than .10) on fertility (number of ewes lambing of ewes bred), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…30 In another study, ewes injected with Se subcutaneously (4 mg each month for 2 years) had increased preweaning survival of lambs. 31 Thus, these studies suggest that Se administration to sheep receiving marginally deficient dietary Se 31 or adequate dietary Se 30 improves the immune response, thereby raising their defenses to infectious agents, with subsequent effects on productivity.…”
Section: Discussionmentioning
confidence: 89%
“…30 In another study, ewes injected with Se subcutaneously (4 mg each month for 2 years) had increased preweaning survival of lambs. 31 Thus, these studies suggest that Se administration to sheep receiving marginally deficient dietary Se 31 or adequate dietary Se 30 improves the immune response, thereby raising their defenses to infectious agents, with subsequent effects on productivity.…”
Section: Discussionmentioning
confidence: 89%
“…Most studies first injected Se either before or shortly after mating. Kott et al (1983) gave monthly injections of sodium selenite (140 mg Se per day) throughout gestation that increased blood Se from approximately 40 to 160 mg Se/l. Thus control ewes were marginal in status.…”
Section: Ironmentioning
confidence: 99%
“…Most reports administered one or more injections of vitamin E by injection from about 4 weeks before the expected date of lambing. The exception was Kott et al (1983) who injected vitamin E at monthly intervals from mating (8.3 mg a-tocopherol per day) and observed an increase in lamb vigour. However, no data were given for vitamin E status of the ewes.…”
mentioning
confidence: 99%
“…Naziroglu et al 27 have shown that selenium, vitamin E, copper (both of which are antioxidants) magnesium and phosphorus are signi®cantly lower in the plasma of aborted ewes compared with non-aborted animals. The administration of selenium before mating and throughout the pregnancy increased selenium levels and the activity of glutathione-Px 26,28 , and dramatically reduced the incidence of barren ewes, while substantially increasing the percentage of lamb crop 29,30 . In humans the problem with reproductive performance is not so evident.…”
Section: Discussionmentioning
confidence: 99%